PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR MATERI BERWUDHU PESERTA DIDIK KELAS 1 SD NEGERI 1 KARANGNONGKO - Fahyuna, Ina; Marno, Marno; Zuhriyah, Indah Aminatuz (Muta'allim: Jurnal Pendidikan Agama Islam, 2023)
This research is based on the problem of (a) Can the application of the inquiry learning model improve the learning outcomes of ablution material for class 1 students at SD Negeri 1 Karangnongko (b) How can the application of the inquiry learning model improve the learning outcomes for ablution material for class 1 students at SD Negeri 1 Karangnongko? Meanwhile, the objectives The results of this research are (a) To find out whether the application of the inquiry learning model can improve the learning outcomes of ablution material for class 1 students at SD Negeri 1 Karangnongko (b) To find out the application of the inquiry learning model in improving the learning outcomes for ablution material for class 1 students at SD Negeri 1 Karangnongko . This research uses three rounds of action research. Each round consists of four stages, namely: Planning, Action, observation and reflection. The target of this research is grade 1 students for the 2023-2024 school year. The data obtained is in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analysis, it was found that student learning achievement increased from cycle I to cycle II, namely, pre-cycle (35%), cycle I (65%), cycle III (85%). The conclusion of this research is that the application of the Inquiry learning model has a positive effect on the learning outcomes of grade 1 students at SD Negeri 1 Karangnongko and this learning model can be used as an alternative PAI learning Abstrak Penelitian ini berdasarkan permasalahan (a) Apakah penerapan model pembelajaran inkuiri dapat meningkatkan hasil belajar materi berwudhu peserta didik kelas 1 SD Negeri 1 Karangnongko (b) Bagaimana penerapan model pembelajaran inkuiri dalam meningkatkan hasil belajar materi berwudhu peserta didik kelas 1 SD Negeri 1 Karangnongko Sedangkan tujuan dari penelitian ini adalah (a) Untuk mengetahui penerapan model pembelajaran inkuiri dapat meningkatkan hasil belajar materi berwudhu peserta didik kelas 1 SD Negeri 1 Karangnongko (b) Untuk mengetahui penerapan model pembelajaran inkuiri dalam meningkatkan hasil belajar materi berwudhu peserta didik kelas 1 SD Negeri 1 Karangnongko. Penelitian ini menggunakan penelitian tindakan (action research) sebanyak tiga putaran. Setiap putaran terdiri dari empat tahap yaitu : Perencanaan, Tindakan, observasi dan refleksi. Sasaran penelitian ini adalah siswa kelas 1 Tahun pelajaran 2023-2024. Data yang diperoleh berupa hasil tes formatif, lembar observasi kegiatan belajar mengajar. Dari hasil analis didapatkan bahwa prestasi belajar siswa mengalami peningkatan dari siklus I sampai siklus II yaitu, pra siklus (35%), siklus I (65%), siklus III (85%). Simpulan dari penelitian ini Penerapan model pembelajaran Inkuiri berpengaruh positif terhadap hasil belajar peserta didik kelas 1 SD Negeri 1 Karangnongko serta model pembelajaran ini dapat digunakan sebagai salah satu alternatif pembelajaran PAI.